Analysis Of Traditional Retail Strategies In Facing Modern Retail In Malang City - Prayogi, Tegar; Hana Laylatul Khusnah (International Journal of Entrepreneur and Business Administration, 2024)
This analysis aims to examine the strategies carried out by traditional retailers in Malang City in facing competition with modern retailers. This research uses qualitative methods with data collection techniques through interviews, observations, and literature studies. The results show that traditional retailers in Malang City face various challenges from modern retailers, such as lower prices, greater product variety, and better service. To face these challenges, traditional retailers implement various strategies, such as: Strengthening personal service and hospitality, Offering unique and distinctive products, Building local communities and networks, Improving management efficiency and effectiveness, Utilizing information and communication technology, The government also needs to play a role in helping traditional retailers to improve their competitiveness, such as by providing training, coaching, and access to capital.